International Society for Heart and Lung Transplantation consensus statement for the standardization of bronchoalveolar lavage in lung transplantation - Martinu, Tereza (J Heart Lung Transplant, 2020)
Bronchoalveolar lavage (BAL) is a key clinical and research tool in lung transplantation (LTx). However, BAL collection and processing are not standardized across LTx centers. This International Society for Heart and Lung Transplantation–supported consensus document on BAL standardization aims to clarify definitions and propose common approaches to improve clinical and research practice standards. The following 9 areas are covered: (1) bronchoscopy procedure and BAL collection, (2) sample handling, (3) sample processing for microbiology, (4) cytology, (5) research, (6) microbiome, (7) sample inventory/tracking, (8) donor bronchoscopy, and (9) pediatric considerations. This consensus document aims to harmonize clinical and research practices for BAL collection and processing in LTx. The overarching goal is to enhance standardization and multicenter collaboration within the international LTx community and enable improvement and development of new BAL-based diagnostics.